Rummaging through the Attic of New England. Issue 1 (25th January 2019) - Berry, Brieanne; Bonnet, Jennifer; Isenhour, Cindy
The concept of the circular economy has taken off, gaining momentum along with concerns about resource depletion, waste, and the impending 'end of cheap nature' (Moore 2014 ). Environmentalists and industrialists alike have promoted the benefits of reuse as a means toward improved efficiency and reduced resource pressure. Some have called for a new 'culture of reuse' (Botsman and Rogers 2010 ;Stokes et al. 2014 ). It is in this context that we explore repair, resale, and reuse as practices with deep historical precedent and contemporary continuity. Are there lessons to be learned from places that are already home to circular economies and strong cultures of reuse? And are there dangers inherent in a stronger, more formalized reuse sector? This paper draws on an historical and ethnographic analysis of vibrant reuse practices in the rural northeastern state of Maine. While there is a popular tendency to explain Maine's persistent reuse practices as a response to economic and geographic marginality, our empirical observations suggest that these explanations do not adequately capture the complexity of reuse markets, discount the power of human agency and sense of place, and preclude important lessons for reuse policy in other contexts. Insights from Maine suggest that any effort to promote reuse would benefit from looking beyond purely economic rationales to attend to matters of place, sociality, and market relationality.